OPPORTUNITIES, TEACHERS’ ATTITUDE AND ENGAGEMENT IN CONTINUING PROFESSIONAL DEVELOPMENT (CPD) ACTIVITIES - Gonzaga, Elvie Barzo (International Journal of Research -GRANTHAALAYAH, 2024)
This descriptive research investigated the opportunities, attitude, and engagement in Continuing Professional Development (CPD) activities among elementary school teachers in the Province of Iloilo for the school year 2023-2024. The population comprised of elementary school teachers, with 380 participants selected through random sampling. Data were collected through an online survey utilizing a structured, researcher-made, validated and reliability tested questionnaire. The results revealed significant differences in the opportunities for CPD activities across congressional districts. Additionally, significant variations were found in teachers’ attitude towards CPD activities based on their educational attainment. Furthermore, significant differences were observed in the level of teachers’ engagement in CPD activities concerning both educational attainment and congressional district. However, no significant differences were found when teachers were classified according to their age, sex, school level, and school size. This study concludes that, while opportunities and attitude significantly influence engagement in CPD activities, their significant differences vary when they were classified according to their educational attainment and congressional district. Hence, it is imperative to consider these when designing CPD programs for elementary school teachers in the Province of Iloilo. Tailoring CPD opportunities and strategies is highly recommended to address the specific needs and preferences of teachers based on their educational backgrounds and geographic locations. Moreover, further research is warranted to explore additional variables that may influence teachers’ engagement in CPD activities and to assess the long-term effectiveness of CPD programs in enhancing teaching quality and student outcomes.